A New Cytotoxic Steroidal Glycoalkaloid from the Methanol Extract of Blumea lacera Leaves - Raushanara Akter; Shaikh J. Uddin; Joe Tiralongo; I. Darren Grice; Evelin Tiralongo (Frontiers Media S.A., 2015)
PURPOSE: Blumea lacera (B. lacera) (Asteraceae) is a well-known Bangladeshi medicinal plant. This study aimed to identify and characterize constituents associated with the significant cytotoxic activity of this plant that we reported previously. Here, we describe the isolation and characterization of a new steroidal glycoalkaloid (SGA) 1, the evaluation of its cytotoxic activity, apoptotic potential, and effect on cell cycle in comparison to analogous steroidal glycoalkaloids (SGAs). METHODS: SGA 1 was isolated using C18 SPE and HPLC, and subsequently structurally characterized using 1D and 2D NMR, MS and other spectroscopic methods, along with a comparative inspection of the literature. Cytotoxic activity of 1 and seven SGA analogues and steroidal alkaloids (SAs), (β-solamarine, α-solanine, β-solamargine, α-solasonine, khasianine, solasodine, tomatidine HCl) were evaluated for their cytotoxicity against two healthy (NIH3T3 and VERO) and four human cancer (AGS, HT-29, MCF-7 and MDA-MB-231) cell lines using the MTT assay. Cytotoxic SGAs were further evaluated for apoptosis-inducing potential and cell cycle arresting ability against breast cancer cells (MCF-7) using the FITC Annexin V and propidium iodide (PI) assay. RESULTS: Bioactivity guided fractionation of the methanol extract of B. lacera led to isolation of compound 1: (25R)-3β-{O-β-D-glucopyranosyl-(1→4)-O-α-L-rhamnopyranosyl-(1→4)-[O-α-L-rhamnopyranosyl-(1→2)]-α-L-rhamnopyranosyl}-22αN-spirosol-5-ene. SGA 1 was the most cytotoxic compound against a number of human cancer cell lines with an IC50 of 2.62 µM against MCF-7 cells. It displayed the highest apoptotic potential (32% AV+/PI-) on MCF-7 cells compared to other cytotoxic SGA analogues and a slight, but significant cell cycle arresting effect. CONCLUSIONS: A new SGA 1 was isolated from B. lacera and its cytotoxic activity, as well as that of other SAGs, was evaluated. SAR investigations on SGA 1, in relation to SGA analogues, show that the number and nature of sugar moieties along with the linkages of the sugar to the aglycone are crucial for cytotoxic and apoptotic activity.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.